Design, synthesis and application of benzyl‐sulfonate biomimetic affinity adsorbents for monoclonal antibody purification from transgenic corn. Issue 1 (17th December 2013) - Maltezos, Anastasios; Platis, Dimitris; Vlachakis, Dimitrios; Kossida, Sophia; Marinou, Marigianna; Labrou, Nikolaos E.
<x xml:space="preserve">Abstract</x> The human anti‐human immunodeficiency virus (HIV) antibody 2G12 (mAb 2G12) is one of the most broadly neutralizing antibodies against HIV that recognizes a unique epitope on the surface glycoprotein gp120. In the present work, a limited affinity‐ligand library was synthesized and evaluated for its ability to bind and purify recombinant mAb 2G12 expressed in transgenic corn. The affinity ligands were structural fragments of polysulfonate triazine dye Cibacron Blue 3GA (CB3GA) and represent novel lead scaffolds for designing synthetic affinity ligands. Solid phase chemistry was used to synthesize variants of CB3GA lead ligand. One immobilized ligand, bearing 4‐aminobenzyl sulfonic acid (4ABS) linked on two chlorine atoms of the triazine ring (4ABS‐Trz‐4ABS), displayed high affinity for mAb 2G12. Absorption equilibrium, 3D molecular modelling and molecular dynamics simulation studies were carried out to provide a detailed picture of the 4ABS‐Trz‐4ABS interaction with mAb 2G12. This biomimetic affinity ligand was exploited for the development of a facile two‐step purification protocol for mAb 2G12. In the first step of the procedure, mAb 2G12 was purified on an S‐Sepharose FF cation exchanger, and in the second step, mAb 2G12 was purified using affinity chromatography on 4ABS‐Trz‐4ABS affinity adsorbent. Analysis of the antibody preparation by sodium dodecyl sulfate‐polyacrylamide gel electrophoresis and enzyme‐linked immunosorbent assay showed that the mAb 2G12 was fully active and of sufficient purity suitable for analytical applications. Copyright © 2013 John Wiley & Sons, Ltd.